Queue system analysis and feasibility layout at Pekanbaru toll gate service - Muhammad Farhan Fatikala; Iwan Nauli Daulay; Anggia Paramitha (Operations Management and Information System Studies, 2022)
This research aims to find out and help improve the effectiveness of the queuing system and the feasibility of the layout at the Pekanbaru Toll Gate service by using quantitative analysis of queuing and layout models. From the observations made, it is known that the queuing pattern that occurs at the Pekanbaru Toll Gate uses a single channel-single phase (M/M/1) model. The results showed that the average number of vehicles at the entrance is 6 vehicles and the utilization rate is 85.6269%, while at the exit the average number of vehicles is 13 and the utilization rate is 92,6829%. For the feasibility of the layout at the entrance, it has met the vehicle capacity, but at the exit it still has not met the vehicle capacity because it exceeds the existing queue line limit.